Kilka uwag o listach dyktowanych Wincentego Pola z lat 1867 i 1869 - Myszor-Ciecieląg, Monika (Colloquia Litteraria, 2012)
Some Remarks on Wincenty Pol’s dictated letters from 1867 and 1869 The article deals with the issue of ‘the dictated letter’ in scholarly editing practice. The author presents the background of the letters mentioned in the title and examines the question of letters dictated by blind people in terms of their credibility as a means of communication. She points to various difficulties an editor has to face when preparing similar texts for printing.